Urolithiasis Bioresource. (24th July 2014) - Parreira, Bruna; Seidi, Mónica; Couto, Ana Rita; Meneses, Raquel; Lima, Manuela; Rodrigues, Raul; Ribeiro, Maria; Bruges-Armas, Jácome
Urolithiasis is frequent and raises significant health care burden in a working-age population. Its prevalence, in the Azores archipelago, is currently unknown but it is thought to be higher than the overall estimated prevalence. The Azores Biobank (AZORBIO) Urolithiasis samples have been collected in accordance with standard operation procedures (SOPs) to ensure high quality. Each donor provided 30 ml whole blood and 9 ml of urine. If possible, we preferred blood collected from fasting individuals and first morning urine samples. Aliquots of plasma, serum, DNA, RNA and urine, are stored at -80°C freezers. This collection of samples, and data, will be used to investigate the genetic and/or environmental risk factors associated with the disease in this geographical area.